Was ist von der Familienpolitik der Großen Koalition zu erwarten? - C. Katharina Spieß; Holger Bonin; Holger Stichnoth; Stefan Bauernschuster; Anita Fichtl; Martin Werding (Wirtschaftsdienst, 2014)
Der Koalitionsvertrag sieht zwar keine weitreichenden familienpolitischen Maßnahmen vor. Allerdings sollen die Kindertagesbetreuung und das Elterngeld weiter ausgebaut werden. Damit folgt die Große Koalition zumindest teilweise einer Studie mehrerer Wirtschaftsforschungsinstitute, die alle bestehenden familienpolitischen Leistungen einer Effizienzanalyse unterzogen und umfassend bewertet hatte. – – A major evaluation of family policies in Germany came to the primary conclusions that family leave and early childhood education and care policies are effective. Specific German tax regulations, however, are less effective, as they decrease the incentives, especially for mothers, to return to the labour market or increase the number of hours they work. The tax regulations for couples, in particular, should be reformed, as this would offer funding possibilities for other worthwhile policies. However, it should not be forgotten that tax regulations are not just aimed at family policies. Indeed, their primary function is to reduce the burden on families and to keep them out of poverty, as demanded by the Germany Federal Constitutional Court. Given the fi ndings of this evaluation, the new German government plans to implement policies which make sense but which do not go far enough. Public child care has been shown to increase maternal employment, household income and fertility in Germany. There are good reasons to invest further in public child care for young children; however, the focus should not only be on the quantity but also the quality of care.
Keywords: H24; I38; J13; J16; 330; Familienleistungsausgleich; Familienpolitik; Regierungskoalition; Deutschland